2016
DOI: 10.1128/aac.01471-15
|View full text |Cite
|
Sign up to set email alerts
|

Neutropenia Associated with Long-Term Ceftaroline Use

Abstract: dCeftaroline is a fifth-generation cephalosporin with potent antimicrobial activity against Gram-positive and Gram-negative pathogens. Neutropenia is a rare serious adverse event for the class of cephalosporins; however, we observed several cases of severe neutropenia in our outpatient infectious disease practice believed to be associated with ceftaroline use. The aim of this study was to determine the incidence of neutropenia among patients receiving ceftaroline therapy for more than 7 days. We conducted a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 27 publications
3
39
0
Order By: Relevance
“…This study found that prolonged ceftaroline exposure is an independent risk factor for developing neutropenia when compared to ceftriaxone; most neutropenia cases were mild and resolved with cessation of the offending β‐lactam. Patients within a lower BMI stratum (i.e., 18.5–25 kg/m 2 ) were also more likely to develop neutropenia, a finding supported by other literature . In most scenarios, ceftaroline was used empirically in culture‐negative infections, which may be suggestive of using a single antibiotic agent to facilitate transitions of care in scenarios where MRSA and Enterobacteriales are suspected.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This study found that prolonged ceftaroline exposure is an independent risk factor for developing neutropenia when compared to ceftriaxone; most neutropenia cases were mild and resolved with cessation of the offending β‐lactam. Patients within a lower BMI stratum (i.e., 18.5–25 kg/m 2 ) were also more likely to develop neutropenia, a finding supported by other literature . In most scenarios, ceftaroline was used empirically in culture‐negative infections, which may be suggestive of using a single antibiotic agent to facilitate transitions of care in scenarios where MRSA and Enterobacteriales are suspected.…”
Section: Discussionsupporting
confidence: 67%
“…However, adverse effects related to ceftaroline use are rarely described. Multiple observational and case report studies have suggested that ceftaroline exposure is associated with higher rates of neutropenia than seemingly listed in the product package insert . The prolonged use of ceftaroline in off‐label, difficult‐to‐treat clinical scenarios may potentiate the risk of neutropenia and contribute to additional patient morbidity and mortality, particularly if adequate follow‐up laboratory monitoring is not performed …”
mentioning
confidence: 99%
“…Two recent studies observed neutropenia in 67 patients when ceftaroline was used ≥2 weeks in duration (10–14% neutropenia) and ≥3 weeks in duration (21% neutropenia) [14]. Another study observed that 18% of their 39 patients experienced neutropenia; patients received ceftaroline for a median of 27 days [15]. Both studies recommended close laboratory monitoring with long-term ceftaroline use.…”
Section: Discussionmentioning
confidence: 99%
“…Study data were limited to inpatient records; thus, efficacy and safety endpoints reflect short-term data. Notably, neutropenia may be underrepresented, considering that this reaction is known to occur with prolonged ceftaroline administration (33). This analysis included three academic medical centers, and it is unclear if these findings apply to other sites with differing patient populations and practice patterns.…”
Section: Discussionmentioning
confidence: 99%